2022
DOI: 10.1097/brs.0000000000004506
|View full text |Cite
|
Sign up to set email alerts
|

Reoperation and Perioperative Complications after Surgical Treatment of Cervical Radiculopathy: A Comparison between Three Procedures

Abstract: Study Design. A retrospective database study.Objective. The purpose of our study was to compare the perioperative complications and reoperation rates after anterior cervical discectomy and fusion (ACDF), cervical disk arthroplasty (CDA), and posterior cervical foraminotomy (PCF) in patients treated for cervical radiculopathy. Summary of Background Data. Cervical radiculopathy results from compression or irritation of nerve roots in the cervical spine. While most cervical radiculopathy is treated nonoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…It was therefore refreshing to see the publication of the current retrospective study from Washington (USA) , which compared the revision rates and complications seen in these three procedures. 7 The surgeons used the PearlDiver Patient Record Database to identify cases of cervical radiculopathy that underwent ACDF, cervical disc arthroplasty (CDA), or PCF at one or two levels from 2007 to 2016. The outcomes assessed were coded complications, which includes the majority of outcomes of interest, but no actual functional or pain scores.…”
Section: Surgery For Cervical Radiculopathy: What Is the Complication...mentioning
confidence: 99%
“…It was therefore refreshing to see the publication of the current retrospective study from Washington (USA) , which compared the revision rates and complications seen in these three procedures. 7 The surgeons used the PearlDiver Patient Record Database to identify cases of cervical radiculopathy that underwent ACDF, cervical disc arthroplasty (CDA), or PCF at one or two levels from 2007 to 2016. The outcomes assessed were coded complications, which includes the majority of outcomes of interest, but no actual functional or pain scores.…”
Section: Surgery For Cervical Radiculopathy: What Is the Complication...mentioning
confidence: 99%
“…28 Estimated rate of revision surgery after CDR ranges from 1% to 15% dependent on the study and follow-up time. 23,[29][30][31] Skovrlj et al 30 reports that from a total of 1068 cervical arthroplasty levels operated on with a mean follow-up of 2.3 years (range, 2-4 y), the established mean rate of reoperation (laminoforaminotomy, laminectomy, and/or posterior fusion ) is 1.0% (range, 0%-3.1%), revision (adjusting or modifying original implant) at 0.2% (range, 0%-0.5%), and removal (often followed by ACDF) at 1.2% (range, 0%-1.9%). In a multicenter analysis by Lee et al, 32 3350 primary CDR procedures between 2008 and 2017 were studied with an arthroplasty removal rate of 2.1%.…”
Section: Utilization Of Pcf For Persistent/ Recurrent Symptoms After Cdrmentioning
confidence: 99%
“…In a recent retrospective review that included 507-patient propensity matched cohorts, one for ACDF, PCF, and CDR, the rate of revision surgeries was significantly higher among CDR patients than ACDF or PCF (6.9% vs. 3.16% vs. 3.55%, respectively). 31 CDR can present implant-related complications. Quan et al 34 reported a case of posterior migration of the implant, whereas Hrabálek et al 35 reported no implantrelated complications, such as migration, loosening, or subsidence; however, the Hrabaĺek et al 35 study was limited by its small sample size.…”
Section: Utilization Of Pcf For Persistent/ Recurrent Symptoms After Cdrmentioning
confidence: 99%
See 2 more Smart Citations